2007
DOI: 10.1073/pnas.0609315104
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial clock, a stable phase oscillator with negligible intercellular coupling

Abstract: Accuracy in cellular function has to be achieved despite random fluctuations (noise) in the concentrations of different molecular constituents inside and outside the cell. The circadian oscillator in cyanobacteria is an example of resilience to noise. This resilience could be either the consequence of intercellular communication or the intrinsic property of the built-in biochemical network. Here we investigate the intercellular coupling hypothesis. A short theoretical depiction of interacting noisy phase oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…These data, coupled with mathematical modeling, suggest that the TTFL is required for the generation of robust circadian oscillations specifically under conditions of rapid growth (61,62). In contrast to what is observed in eukaryotic systems, the phasing of the cyanobacterial clock is inherited from mother cell to daughter cell with negligible intercellular coupling (63,64). Combined, these results would suggest that the fidelity of cellular phase is compromised in individual cells without the TTFL.…”
Section: Regulation Of the Kai-based Oscillatormentioning
confidence: 82%
“…These data, coupled with mathematical modeling, suggest that the TTFL is required for the generation of robust circadian oscillations specifically under conditions of rapid growth (61,62). In contrast to what is observed in eukaryotic systems, the phasing of the cyanobacterial clock is inherited from mother cell to daughter cell with negligible intercellular coupling (63,64). Combined, these results would suggest that the fidelity of cellular phase is compromised in individual cells without the TTFL.…”
Section: Regulation Of the Kai-based Oscillatormentioning
confidence: 82%
“…However, we cannot exclude the possibility that the rhythmic transcription is indirectly induced in the heterocyst by time-dependent intercellular signals from oscillators in neighboring vegetative cells. Single-cell imaging analysis in Synechococcus has demonstrated that the synchronization among cells is negligible, and instead, the intracellular timing mechanism is extremely robust and precise (39,40). In contrast, it has been suggested that in multicellular eukaryotes, cell-to-cell communication is important in synchronizing each clock cell into a robust oscillatory system at the tissue or organ level (41,42).…”
Section: Fig 2 Genome-wide Circadian Transcription Profiles Under Ll mentioning
confidence: 99%
“…In multicellular organisms, the robustness might be explained by intercellular interactions (3,4), but it is now known that even unicellular organisms can have very stable circadian rhythms. The clock of the cyanobacterium Synechococcus elongatus, for example, has a correlation time of several months (5), even though the clocks of the different cells in a population hardly interact with one another (5,6). How circadian clocks can be so stable even at the single cell level is not understood.…”
mentioning
confidence: 99%